2021
DOI: 10.21608/ejhm.2021.178593
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in Women Using Levonorgestrel Releasing Intrauterine System

Abstract: Background: The effect of levonorgestrel-releasing intrauterine system (LNG IUS) on metabolic parameters like body mass index, body weight, blood pressure, blood sugar, lipid profile and liver function test is still unclear. Objective: To assess the possible metabolic effects of the levonorgestrel intrauterine system on serum lipids, body weight and fasting blood glucose level after a period of six months. Subjects and Methods: A prospective study comprised 50 women attended to the Department of Family Plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…In our results, we observed no statistically significant variances among the examined groups regarding anthropometrics and CBC. In accordance with our results, Rezk et al (16) documented that no statistically significant variance was found among the examined groups in terms of anthropometrics (weight, height, BMI, & WC). Also, Hoseini et al (17) purposed to evaluate the acceptability of LNG & the Yuzpe regimen among Iranian women by examining the adverse reactions & the subsequent changes in the quantity & pattern of menstruation.…”
Section: Resultssupporting
confidence: 93%
“…In our results, we observed no statistically significant variances among the examined groups regarding anthropometrics and CBC. In accordance with our results, Rezk et al (16) documented that no statistically significant variance was found among the examined groups in terms of anthropometrics (weight, height, BMI, & WC). Also, Hoseini et al (17) purposed to evaluate the acceptability of LNG & the Yuzpe regimen among Iranian women by examining the adverse reactions & the subsequent changes in the quantity & pattern of menstruation.…”
Section: Resultssupporting
confidence: 93%